Unraveling the effects of cultural diversity in teams: A retrospective of research on multicultural work groups and an agenda for future research - Stahl, Günter K; Maznevski, Martha L (Journal of International Business Studies, 2021)
Our 2010 Journal of International Business Studies article, “Unraveling the Effects of Cultural Diversity in Teams: A Meta-analysis of Research on Multicultural Work Groups,” attempted to take stock of existing research on cultural diversity in teams, to reconcile conflicting perspectives and past results, and provide a better understanding of the mechanisms and boundary conditions under which diversity affects team outcomes. To guide our analysis, we developed a theoretical framework outlining how cultural diversity leads to both process gains and losses in teams, and specifying the contextual conditions under which diversity contributes to effective team outcomes. We tested our hypotheses in a meta-analysis of research on cultural diversity in teams, encompassing 108 primary studies with a combined sample size of 10,632 work groups. The results suggested that cultural diversity does not have a direct impact on team performance but rather that the effect is indirect, mediated by process variables such as creativity, cohesion, and conflict; and is moderated by contextual influences such as team tenure, the complexity of the task, and whether the team is co-located or geographically dispersed. Unexpected findings raised important questions about the dynamics of diverse teams and underscored the need for further examination. In this Retrospective, we reflect on progress made in research on culturally diverse teams over the last decade, highlight remaining gaps and open questions, and propose an agenda for future research.